The Impact of a Sauna on Post-Exercise Recovery - Dębicki, Filip; Grądalski, Łukasz; Niemirka, Szymon; Janiak, Aleksandra; Dominiczak, Kinga; Kopaczyńska, Adrianna; Szafrańska, Katarzyna (Quality in Sport, 2025)
Regeneration of the body after intense exercise is a key element necessary for the proper process of improving performance and achieving better results in strength training. One of the most important issues in any athlete is the uninterrupted continuation of training and the most optimal regeneration of tissues and the body, which is essential for further improvement of skills and development in a given sport. There are a number of methods to support the repair processes of tissues and help the body fight injuries and micro-injuries that occur during exercise and are an indispensable part of building strength and muscle mass. An example that has recently become very popular in the sports environment is the use of saunas characterized by thermal properties, through which it is possible to influence physiological processes that accelerate the return to form and achieve better results in sports competitions. This form not only helps tissue regeneration, but also relaxes and calms the body, which is stimulated during sports and requires calming afterwards.